2005
DOI: 10.4049/jimmunol.174.8.4789
|View full text |Cite
|
Sign up to set email alerts
|

Functional Requirements for Signaling through the Stimulatory and Inhibitory Mouse NKR-P1 (CD161) NK Cell Receptors

Abstract: The NK cell receptor protein 1 (NKR-P1) (CD161) molecules represent a family of type II transmembrane C-type lectin-like receptors expressed predominantly by NK cells. Despite sharing a common NK1.1 epitope, the mouse NKR-P1B and NKR-P1C receptors possess opposing functions in NK cell signaling. Engagement of NKR-P1C stimulates cytotoxicity of target cells, Ca2+ flux, phosphatidylinositol turnover, kinase activity, and cytokine production. In contrast, NKR-P1B engagement inhibits NK cell cytotoxicity. Nonethel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
33
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 39 publications
1
33
0
Order By: Relevance
“…NKR-P1F contains a transmembrane arginine that indicates that it may interact with an ITAM-containing adaptor such as FcRγ [32], but previous attempts to demonstrate an activating function for mouse NKR-P1F has been inconclusive [31]. As shown in Figure 2A, we observed a distinct Ca 2+ -response in NK cells in response to NKR-P1F cross-linking, but weaker than NKR-P1A.…”
Section: Nkr-p1f Activation Induces Redirected Lysis and A Robust Calsupporting
confidence: 47%
“…NKR-P1F contains a transmembrane arginine that indicates that it may interact with an ITAM-containing adaptor such as FcRγ [32], but previous attempts to demonstrate an activating function for mouse NKR-P1F has been inconclusive [31]. As shown in Figure 2A, we observed a distinct Ca 2+ -response in NK cells in response to NKR-P1F cross-linking, but weaker than NKR-P1A.…”
Section: Nkr-p1f Activation Induces Redirected Lysis and A Robust Calsupporting
confidence: 47%
“…The molecular mechanisms of signal transduction via human NKR-P1A are unclear. The cytoplasmic tail of human NKR-P1A does not contain the CxCP/S/T lck-binding motif found in CD4, CD8, and rodent NKR-P1 (4,5,14). Although it has been reported that human NKR-P1A can be found in association with src family kinases, including p56 lck (17), others report a failure to reproduce these observations (5).…”
mentioning
confidence: 74%
“…Immunoreactive bands were developed using HRP-conjugated secondary Abs (DakoCytomation) and chemiluminescent substrate (ECL Plus; Amersham Biosciences). For assays of enzymatic activity, the beads were equilibrated in aSMase or nSMase buffer, without detergent, and then incubated for 2 h at 37°C in a final volume of 150 ml in the presence of 454 pmol of [N-methyl- 14 C]sphingomyelin (specific activity 55 mCi/mmol; Amersham Biosciences). Radioactive phosphocholine produced from 14 C-labeled sphingomyelin was extracted and quantitated as indicated below.…”
Section: Immunoprecipitation and Immunoblottingmentioning
confidence: 99%
See 2 more Smart Citations